PENYESUAIAN DIRI PADA MASA PUBERTAS - Lilis Suryani, Lilis Suryani (Konselor, 2013)
At puberty adolescents undergo physical and psychological changes. Teens should be able to adjust to the changes that occur during puberty in him of receiving a physical condition and use it effectively. The fact in the school still many young people who have not been able to adjust to the changes that occur in the body. The purpose of this study is reveal the adjustment of adolescents during puberty. This research is descriptive. The population study of students from class VII, VIII and IX MTsN Langsat Kadap Pasaman listed in the 2012-2013 school year as many as 1090 people. The research sample is representative of the population number of students drawn using stratified random sampling technique with a sample of 92 people. The instruments used in the data collection was a questionnaire and processed using simple statistics that percentage.